Application of DCE-US using the LI-RADS for patients with liver nodules at high risk for hepatocellular carcinoma: A preliminary study and comparison with visual interpretation. Issue 155 (October 2022) - Qiu, Shibo; Ding, Jianmin; Qin, Zhengyi; Zhou, Yan; Zhou, Hongyu; Wang, Yandong; Zhao, Lei; Jing, Xiang
Abstract: Objective: To explore the value of dynamic contrast-enhanced ultrasound (DCE-US) for the Liver Imaging Reporting and Data System (LI-RADS). Methods: We included 220 liver nodules at high risk for hepatocellular carcinoma (HCC) from January 2019 to October 2021. Visual interpretation and DCE-US-based quantitative categories using VueBox® software were compared for consistency, nodule enhancement intensity, and washout onset following the contrast-enhanced ultrasound LI-RADS. Taking the cut-off value of the ROC curve on washout onset as the time criterion of early washout of LR-M nodules, analyzed the diagnostic performance of LR-5 for HCC and compared it to that of washout onset within 60 s. Results: The LI-RADS visual and DCE-US interpretation results showed good consistency (Kappa = 0.730), but differed significantly in determining the LR-5 washout onset (91.2 ± 30.2 vs. 82.0 ± 32.8 s, P  = 0.020) and detecting early washout (<60 s) in 196 nodules ( P  = 0.047). Distinguishing HCC from non-HCC malignancies had: area under the ROC curve, 0.85 (95 % confidence interval, 0.8–0.9); Youden index, 0.69; cut-off value, 48 s; sensitivity, 74.4 %; specificity, 95.0 %. When LR-M diagnosis used washout onset within 48 s, LR-5 diagnosis had sensitivity, 72.8 %; specificity, 95.0 %; positive predictive value, 98.5 %; showing a higher sensitivity than with washout onset in 60 s (62.2 %; P  = 0.033). Conclusion: DCE-US and visual interpretations showed high consistency in LI-RADS categories but differed in assessing the washout time. According to the DCE-US interpretation, the diagnostic performance of LR-5 could be improved using washout onset of 48 s for LR-M.